Oxidative stress in the heart of rats infected with Trypanosoma Evansi - Baldissera M.D. (2016)
© 2016, Korean Society for Parasitology and Tropical Medicine.This study was conducted to investigate the occurrence of oxidative stress in the heart tissue of rats infected with Trypanosoma evansi. Rats were divided into 2 groups (A and B) with 12 animals each, and further subdivided into 4 subgroups (A1 and A2, 6 animals/each; and B1 and B2, 6 animals/each). Animals in the groups B1 and B2 were subcutaneously inoculated with T. evansi. Thiobarbituric acid reactive substances (TBARS), superoxide dismutase activity (SOD), glutathione S-transferase activity (GST), reduced glutathione activity (GSH), and non-protein thiols (NPSH) in the heart tissue were evaluated. At day 5 and 15 post-infection (PI), an increase in the TBARS levels and a decrease in the SOD activity (P<0.05) were observed. GSH and GST activities were decreased in infected animals at day 15 PI (P<0.05). Considering the proper functioning of the heart, it is possible that the changes in the activity of these enzymes involved in the oxidative stress may be related, at least in part, in the pathophysiology of rats infected with T. evansi.